West Australian parents' views on vaccinating their children against COVID-19: a qualitative study - Samantha J. Carlson; Katie Attwell; Leah Roberts; Catherine Hughes; Christopher C. Blyth (BMC, 2023)
Abstract Background Australian children and adolescents were among the last local cohorts offered COVID-19 vaccines. Despite promising initial uptake, coverage subsequently plateaued, requiring further efforts to improve access and build parents' recognition of the importance of COVID-19 vaccination. We sought to understand West Australian (WA) parents' willingness to vaccinate their children to inform strategies for improving uptake at the time in which they were becoming eligible. Methods We undertook in-depth qualitative interviews with 30 parents of children aged 5-17 years from June - December 2021. During this period, children aged 12-15 years became eligible for vaccination; children aged 5-11 years became eligible shortly thereafter. Data were thematically analysed in NVivo. Results Most parents intended on vaccinating their children once eligible. Parents sought to protect their children, to protect the community, to resume travel, and to get back to "normal". They reflected that vaccination against key infectious threats is a routine activity in childhood. Some were concerned about the vaccine, particularly mRNA vaccines, being new technology or impacting fertility. "Wait-awhiles" wanted to see what other parents would do or were delaying until they felt that there was a higher risk of COVID-19 in WA. Most parents of younger children wanted their child to be vaccinated at the general practice clinic due to familiarity and convenience. Parents were particularly eager for clear and consistent messaging about vaccination of children and adolescents, including safety, importance, scientific evidence, and personal stories. Conclusion For future pandemic vaccinations pertaining to children, governments and health officials need to address parents' concerns and meet their preferences for the delivery of the vaccine program to children and adolescents.